Trend Halal Food di Kalimantan Timur - Hervina Hervina (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2017)
Current developments in food technology have caused the complexity of knowledge about halal food products. This has, among other things, triggered consumer awareness of halal products, and followed the wishes of producers to fulfill the right to halal food globally. This trend not only penetrated Muslim-majority countries, even developed countries (non-Muslims) also began to develop this system. In this study, the author will dig deeper by focusing on how the halal food trend and the implementation of the halal food trend in home industries in the Samarinda and Balikpapan regions. Based on the findings of data in the field of all food products in two places that are the focus of research researchers, Samarinda and Balikpapan are halal food products. Halal food products that are processed are in the form of crackers, cakes and abon, whose basic ingredients are animal origin. Basically, the food manager set the standard for halal production based on Islamic shari'a. Subjects that can raise problems or in this case the author uses the term subhat is the standard of processing raw materials. Such as the fish used are fish that are dead and may seem rotten (poor quality), or use preservatives that do not use the BPPOM standard. There is a tendency, when raw material prices rise, the quality of the product decreases because the owner does not want to raise prices.